2023
DOI: 10.1177/23312165221148022
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Sound Coding Strategies to Make Singing Music More Accessible for Cochlear Implant Users

Abstract: Cochlear implants (CIs) are implantable medical devices that can partially restore hearing to people suffering from profound sensorineural hearing loss. While these devices provide good speech understanding in quiet, many CI users face difficulties when listening to music. Reasons include poor spatial specificity of electric stimulation, limited transmission of spectral and temporal fine structure of acoustic signals, and restrictions in the dynamic range that can be conveyed via electric stimulation of the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Music perception can be assessed by means of several different tests, such as the intelligibility of the lyrics. Some studies have observed that CI users make use of the lyrics in music to identify and enjoy music [ 21 ], as well as to compensate for poor timbre, pitch, and melody identification [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Music perception can be assessed by means of several different tests, such as the intelligibility of the lyrics. Some studies have observed that CI users make use of the lyrics in music to identify and enjoy music [ 21 ], as well as to compensate for poor timbre, pitch, and melody identification [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Buyens et al concluded that enhancing vocals by 6 dB relative to the background instruments led to greater enjoyment of music by CI users [ 25 ]. Accordingly, it was hypothesized that reducing the complexity of the backing music may assist the noise reduction algorithm of the CI sound coding strategy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation